POST OPERATIVE HYPOTHERMIA: INCIDENCE, RELATION TO AGE AND SURGERY - Khan, Sham Sher Ali (Journal of Ayub Medical College Abbottabad, 2000)
Background: The normothermic status of the patients during anesthesia is disturbed and hypothermia is a potential problem. This study was done using Aural thermometry technique to see pattern of post-operative hypothermia. Methods: Patients (n=8Q) core temperature measurements (using aural temperature probes after proper calibration) were obtained in the perioperative period. Results: Sixty-seven patients (83%) had temperature <36°C (mean <35.1°C ± 0.1) on admission to the recovery’ room. This finding of definitive study was supported by an initial finding of the preliminary study (n=103) indicating 89% of the patients with temperature <36°C on admission to the recovery room (mean 34°C ± 0.1). Elderly patients (> 65 years) and patients undergoing surgery of longer duration demonstrated high percentage and most marked decrease in temperature. A significant decrease in temperature, during leaving the reception area and admission to recovery room was found in all the surgical subgroups but the patients undergoing aortic reconstructive surgery showed marked decrease. Most of the patients were discharged with satisfactory rewarming while 20% of patients were discharged from the recovery’ room despite temperature below 36°C.